Effect of genotype and environment on agronomical characters of alfalfa (Medicago sativa L.) in a typical acidic soil environment in southwest China - Tian, Zheng; Yang, Zhengyu; Lu, Zhongjie; Luo, Ben; Hao, Yunfei; Wang, Xiaowen; Yang, Feng; Wang, Song; Chen, Chao; Dong, Rui (Frontiers in Sustainable Food Systems, 2023)
Alfalfa (Medicago sativa L.), an important perennial legume forage crop with high nutritional value and forage yield, is widely used in animal husbandry. However, it is very sensitive to aluminum, which severely limits its growth in acidic soils. In this study, we assessed the genotypic variations in 44 alfalfa varieties in two acidic soil environments and analyzed their phenotypic and genotypic correlations. The results showed that there was significant (P < 0.05) genotypic variation for each trait of the 44 varieties and the genetic diversity was abundant. The average repeatability (R value) of interannual plant height (PH), stem thickness (ST), number of branches (NS), fresh weight (FW), total fresh weight (TFW), and total dry weight (TDW) was high (0.21–0.34), whereas the genetics were relatively stable. PH, NS, FW, TFW, and dry weight (DW) were positively correlated (P < 0.01) with TDW. Six alfalfa varieties (Algonquin, Xinjiang daye, Trifecta, Vernal, WL354HQ, and Boja) with excellent TDW and TFW were identified in different years, environmental regions, and climatic altitudes. Our research results can provide suggestions and critical information regarding the future improvement and development of new alfalfa strains and varieties that are resistant to acidic soil conditions.